Komunikasi Sistem Pembaca 2D Dengan Mesin Laser Marking Berbasis PLC - M. Syafei Gozali (Journal of Applied Electrical Engineering, 2018)
Currently size of Integrated Circuits (IC) become smaller while it needs more information on its label. Therefore 2D data matrix is use to replace standard character for the identification. To improve laser mark machine capabilities to be able to read 2D data matrix, a 2D reader system is required to integrate with existing laser mark machine. This study aims to develop 2D reader system that can read 2D data matrix and communicates with laser mark machine automatically. Communication between 2D reader system and laser mark machine was done through Programmable Logic Control (PLC) inside the machine using serial (RS-232) by utilizes available data memories inside the PLC. The experimental result indicates the 2D reader system able to communicate with laser mark machine and it can differentiate readable and unreadable 2D data matrix. Unreadable 2D Code was caused by different process on the tested material. The readable 2D Code through Chemical Deflash – Water Jet (CD-WJ) process while the unreadable 2D Code run without CD-WJ.